MRI and EEG in Tuberous Sclerosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The relationship between MRI cortical lesion sites and the topographic distribution of EEG spike-and-wave foci was studied in 34 children with tuberous sclerosis at the Service de Neuropediatrie, Hopital Saint Vincent de Paul, Paris, France and the Instituto di Neuropsichiatria Infantile, Roma, Italy.